Histopathological spectrum of lumbar disc changes in obesity: analysis of intervertebral discs in lumbar hernia patients in Zenica-Doboj Canton, Bosnia and Herzegovina - Fatima Juković-Bihorac; Hakija Bečulić; Emir Begagić; Ragib Pugonja; Jovana Radovanović; Amina Džidić-Krivić; Binasa Bašić; Andrej Popov; Haso Sefo; Ermina Iljazović (Medicinski glasnik, 2023)
Aim: To investigate the correlation of body mass index (BMI) with severity of intervertebral disc degeneration. Methods: The study enrolled patients who had undergone surgical intervention for a herniated disc at the Department of Neurosurgery of the Cantonal Hospital Zenica. Patients underwent thorough preoperative evaluation, including medical history, neurological and physical assessments, and radiological analysis. The surgical intervention consisted of a posterior lumbar discectomy, and the excised disc material was preserved and subjected to histopathological analysis based on Histopathologic Degeneration Score (HDS). Patients were divided in two groups according to Body Mass Index (BMI): study group with BMI?25 and control group with BMI<25. Results: Among 69 patients with herniated IVD, 26 (37.7%) were with BMI?25 (study group), and 43 (62.3%) were with BMI<25 (controls). The study group displayed substantial increase in height, 1.80±0.06 m compared to controls, 1.74±0.06 m (p=0.001). Weight and BMI were significantly higher in the study group of patients (weight: 91.60±10.22 vs. 67.37±9.20 kg, BMI: 28±2 vs. 22±2; p<0.001). Differences were confirmed in HDS values in the study group comparing to the control group (p<0.001). The study group exhibited significant differences in chondrocyte proliferation, tears and clefts, granular changes, and mucous degeneration (p<0.05), and positive correlations were found between BMI and these alterations found in the herniated discs (p<0.05). Therefore, HDS showed positive correlations with BMI (R=0.599; p<0.001) and weight (R=0.696; p<0.001). Conclusion: The study's findings confirmed that BMI has a significant impact on intervertebral disc degeneration, emphasizing the importance of weight management in preventing disc degeneration.
Keywords: chondrocyte proliferation; obesity; weight management